The Effectiveness of the Elderly Integrated Healthcare Center Program to Improve Elderly Health - Prisca, Olivia Ingkan; Agustina, Isna Fitria (Indonesian Journal of Public Policy Review, 2024)
The study "Revitalization of the Elderly Posyandu Program in Kebonagung Village, Porong District, Sidoarjo Regency" aimed to describe and analyze the effectiveness of the program using a descriptive qualitative research method. Data was collected through observations, interviews, and documentation, and analyzed using data collection, reduction, presentation, and conclusion. The results showed that the program was effective in terms of program understanding, alignment with objectives, real changes, and achievement of goals. However, the timeliness of the program was not optimal, leading to a lack of routine implementation. The implications of the study highlight the need for improved program scheduling and regularity to maximize the effectiveness of the elderly Posyandu program. The most provocative and very short title that highlights the outcome of the content and makes it appealing to global related scientists could be "Timeliness Key to Effective Elderly Posyandu Program." Highlight : The study aimed to analyze the effectiveness of the Elderly Posyandu Program in Kebonagung Village, Porong District, Sidoarjo Regency using a descriptive qualitative research method. The program was effective in terms of program understanding, alignment with objectives, real changes, and achievement of goals. However, the timeliness of the program was not optimal, leading to a lack of routine implementation. The implications of the study highlight the need for improved program scheduling and regularity to maximize the effectiveness of the elderly Posyandu program. Keywords: Elderly Posyandu Program, Timeliness, Effectiveness, Scheduling, Regularity